Medial Epicanthoplasty: What Works and What Does Not - Baek, Ji Sun; Choi, Young Joo; Jang, Jae Woo (Facial Plastic Surgery, 2020)
Blepharoplasty is the most frequently performed cosmetic surgical procedure in Asia. The epicanthal fold, which is common in Asians, is characterized by a curved skin fold that partially hides the caruncle and lacrimal lake. The epicanthal fold may cause weakening of the esthetic appearance after blepharoplasty. It makes the palpebral fissure height narrower and the length shorter horizontally. Blepharoplasty with epicanthoplasty can enhance the esthetic appearance, but no gold standard surgical technique has been established for epicanthoplasty. Surgeons can choose the surgical technique according to their preference and the patient's characteristics. A carefully designed and fine surgical technique, especially with the use of loupes and tension-free skin closure with the thinnest needle, is required to avoid scarring.
Keywords: epicanthal fold; epicanthoplasty; Asian; double eyelid crease surgery; blepharoplasty